VAGINAL BREECH DELIVERY: STILL A SAFE OPTION - Habib, Sadia; Riaz, Shazia; Abbasi, Nasreen; Ayaz, Attiya; Bibi, Attiya; Parveen, Zahida (Journal of Ayub Medical College Abbottabad, 2013)
Background: Elective caesarean section has replaced vaginal delivery for term breech foetuses due to fear of complications of vaginal breech delivery. This increasing rate of caesarean section worldwide is alarming. It has not only led to increase in adverse consequences in subsequent pregnancies and future fertility but also loss of skills for vaginal breech delivery. This study was conducted to determine the safety of vaginal breech birth in terms of maternal and neonatal complications. Methods: This cross sectional study was conducted at department of Obstetrics/Gynaecology, Ayub Medical College, Abbottabad from January 2004 to December 2011. One seventy-eight women having successful vaginal breech delivery of singleton term foetuses from 2004-2008 were selected. They were studied for neonatal complications like low Apgar score (AS) <7 at 5 min, birth trauma, admission to neonatal intensive care units and perinatal mortality. Maternal complications including any genital tract trauma and post-partum haemorrhage (PPH) were also noted. Results: There were 11243 deliveries during this period, including 674 breech presentations at term (incidence of breech 6%). Out of 178 successful vaginal breech deliveries, 8 (4.49%) neonates had AS <7 at 5 min, and 6 (3.37%) neonates needed NICU admission. There were no cases of birth trauma or perinatal morbidity. Maternal complications occurred in only 5 (2.8%) patients, 2 (1.1%) having perineal tears, 2 (1.12%) retained placenta and one (0.56%) case of post partum haemorrhage. Conclusion: Vaginal breech delivery can be safely undertaken without compromising maternal and neonatal outcome if strict criteria are met before and during labour. Keywords: Vaginal breech delivery, foeto-maternal outcome, breech, delivery